Research, ethics and conflicts of interest - Little, M. (Journal of medical ethics, 1999)
In this paper, I have tried to develop a critique of committee procedures and conflict of interest within research advisory committees and ethical review committees (ERCs). There are specific features of conflict of interest in medical research. Scientists, communities and the subjects of research all have legitimate stakeholdings. The interests of medical scientists are particularly complex, since they are justified by the moral and physical welfare of their research subjects, while the reputations and incomes of scientists depend on the success of their science. Tensions of this kind must at times produce conflict of interest. It is important to recognise that conflicts of interest may unwittingly lead to manipulation of research subjects and their lay representatives on research committees. It is equally important to recognise distinctions between the legal and moral aspects of conflict of interest. Some practical suggestions are made which may go some way towards resolving these difficulties. They indicate what might be needed to ensure the validity of ethical discourse, and to reduce the risks associated with conflict of interest.